Assessment of Fastfood Services in Customer Retention of Janet’s Pares House in Novaliches Bayan, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Janet’s Pares House Offers very reasonable and delicious native cuisine and has also wonover its patrons' hearts and taste senses in a similar fashion to the six major fast food chains.Additionally, it has been a top priority for the locals in the Novaliches region. Where can youfind a flavorful lugaw worth less than ten pesos, and who can resist their pork and chickenbarbeque and their sizzling sisig? Sulit-Sarap ka dito! It should be its appropriatecharacteristic. When customers pay for food, "Sulit" wants to make sure they get value for theirhard-earned cash. A guarantee that their meals will be served by courteous andknowledgeable staff. The mission of "Sarap" is to provide a wide selection of delicious andhigh-quality products.In the Demographic profile of the respondents' gender, most of the females always eat atJanet's, and most Janet’s are those aged 26 and older, and they always visit weekly. In termsof service quality, Janet’s reliability has made most customers very satisfied with the productsbeing served on time. And in tangibility, most of the customers are very satisfied withcompletely designed material such as menus. And the last is responsiveness. Most customersare very satisfied with responding to customers' requests and complaints. In respondents'descriptions of customer retention in food offerings, the customers are very satisfied withcustomer satisfaction with food service, and in customer service, the most satisfied customersare those who listen to their feedback and complaints, and in ambiance, the most satisfiedcustomers are those who are satisfied with the physical environment of a restaurant.The company's reliability, tangibility, and responsiveness should be improved in order toincrease customer retention. And improve their food offerings to ensure customer satisfaction.To be able to retain Janet's customers, researchers would like to recommend a strategy thatcan improve their business for better satisfaction and retention. In business, it is a must tolisten to the customer, be patient, and be understanding to help you communicate effectivelywith the customer. Likewise, businesses need to improve their usability when providingproducts and services. To meet customer retention goals, they need to improve the quality oftheir customer service to improve customer satisfaction.
Keywords: Hospitality Management